Full endoscopic endonasal transsellar-transclival approach: the modularity concept - Pérez-Borredá, Pedro; Simal-Julián, Juan Antonio; de San Román-Mena, Laila Pérez; Botella-Asunción, Carlos (Acta neurochirurgica, 2016)
Background Endoscopic endonasal approaches (EEAs) constitute a reasonable option for the treatment of lesions that involve the sellar and clival regions. Methods We describe, step by step, the full EEA expanded to the middle and lower clivus for the treatment of perisellar lesions. Delimiting different modules around the sellar region is useful in establishing the best endoscopic approach for each tumor. A craniopharyngioma (CP) with clival extension will be used as an illustrative example of the modularity concept of these approaches. Conclusions Transsellar-transclival EEA allows complete resection of lesions located in the sellar and infrasellar region with a low rate of complications.